Pengaruh Variasi Holding Time dan Temperatur Paduan Polipropilena (PP) dengan Serat Sabut Kelapa Terhadap Kekuatan Tarik dan Bending Pada Proses Injection Molding - Nurdin Akbar A; Yuni Hermawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Utilization of composite materials as an alternative to metal materials in the expanding field of engineering. This is because the advantages possessed by Composite materials such as natural fibers into a lighter construction, corrosion resistance, and strength can be designed in accordance with the direction of loading. In this study, the authors make the specimen using coco fiber as a reinforcement of composite and polypropylene as a matrix with the holding time and temperature variations in the injection molding process. The purpose of this study to determine the tensile strength and bending as well as shape analysis and mikroskipis macroscopic fracture that occurs in the specimen by using a camera and microscope test equipment. Variations holding time is 7 seconds, 8 seconds, 9 seconds. Barrel temperature on the injection molding machine used is 180ºC, 190ºC, 200ºC and injection pressure of 7 bar. Of tensile and bending test results it can be concluded that there are significant variations of holding time and temperature on the mechanical properties of the composite strength values ​​were generated. In the holding time and temperature variations, occurring on average values ​​of tensile strength and bending at the highest temperature holding time is 9 seconds 190ºC is 11.42831 N/mm2. and a temperature holding time 8 seconds 180ºC ie 10,584 MPa. Keywords: holding time, temperature, injection molding, tensile strength, bending strength